Mining Companies' Responsibilities to the Environment and Communities Affected by Nickel Downstreaming: A Maslahah Perspective - Salsabila Athirah.R; Cahaya Permata (LP2M IAIN Palopo, 2025)
Nickel downstreaming is part of the national development policy that is expected to have a significant positive impact on the country's economy. However, negative impacts such as environmental damage and the unfulfilled rights of communities around mining areas are crucial due to mining activities, so that the company's legal responsibility for these impacts needs to be studied more deeply. This study aims to examine the impact of nickel downstream mining on the environment and society and the company's legal responsibility viewed from a maslahah perspective. As a normative legal research, the approach used is a legislative and conceptual approach, data collection is carried out through document studies which are then processed and analyzed qualitatively. The results of the study indicate that the impact of nickel downstreaming on the environment causes a reduction in biodiversity, decreased soil fertility and air quality, and the occurrence of river and sea water pollution around the mining site. This also certainly has an impact on the community, both in terms of health, one of which is ISPA, from a socio-economic perspective such as loss of livelihood, as well as from the perspective of customs and culture that distorts traditional rules and norms. Based on the legislation, the company can be held accountable criminally, civilly, and even administratively. This aligns with the principle of maslahah, which requires companies to be responsible. Therefore, companies must provide compensation to the community and improve the environment.